IBN KHALDŪN AND THE JEWS: ON THE IDEA OF RELIGIOUS EMANCIPATION - Epafras, Leonard Chrysostomos (IAIN Kediri, 2017)
The present article is an exploration on Ibn Khaldun’s notion of religious emancipation, notably in the case of Jews in his age. The exploration is based on the examination upon his magnum opus, Muqaddima. Byproduct, it describes as well the dynamic of the notion of religious emancipation and tolerance in history among the Christians and Muslims in the pre-modern era, through which the interreligious relationship is also a concern. Ibn Khaldun was an important fi gure in this endeavor through his sociological analysis of the world history, as his unique overview upon Jews as a marginal religious group. In the present article Ibn Khaldun is situated within his contemporary and considered him as a prominent Islamic thinker in liminality, a condition that allows him to envision new thing but at the same time embedded in the context. Keywords: Ibn Khaldun, the Jews, Religious Emancipation